2018
DOI: 10.15386/cjmed-891
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining Adequate Surgical Margin Status in Breast-Conservation Therapy: Intraoperative Ultrasound-Guided Resection Versus Specimen Mammography

Abstract: Background and aimThe purpose of breast-conserving surgery (BCS) for women with cancer is to perform an oncological radical procedure with disease-free margins at the final histological assessment and with the best aesthetic result possible. Intraoperative resected specimen ultrasound and intraoperative resected specimen mammography may reduce the rates of positive margins and reexcision among patients undergoing conserving therapy. Our objective is to compare the two methods with the histopathological results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Breast ultrasound (BUS) is a quick, reproducible, non-invasive, inexpensive, highly feasible, and highly available method to assess margins. Multiple studies have found that the use of intraoperative BUS as a margin assessment tool reduces the number of positive margins in BCS patients [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Furthermore, Volders et al have shown in a multicenter randomized controlled trial involving 134 patients, that ultrasound-guided BCS also leads to a better cosmetic outcome [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast ultrasound (BUS) is a quick, reproducible, non-invasive, inexpensive, highly feasible, and highly available method to assess margins. Multiple studies have found that the use of intraoperative BUS as a margin assessment tool reduces the number of positive margins in BCS patients [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Furthermore, Volders et al have shown in a multicenter randomized controlled trial involving 134 patients, that ultrasound-guided BCS also leads to a better cosmetic outcome [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for exclusion were as follows: (1) sensitivity and/or speci city data were missing; (2) the paper was not focus on specimen mammography for margin assessment; (3) the paper was published in abstract format only; (4) the paper was a literature review; and /or (5) the paper was not written in English. Eventually, 18 studies were enrolled in the analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
“…These patients require additional interventions for the residual tumor tissue, including re-excision. Therefore, it is crucial to minimize this scenario to improve oncological outcomes, decrease the need for reoperation, and decrease financial healthcare costs [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%